Effect of Tricholoma crassum on growth and productivity of pineapple (Ananas comosus cv. Pattawia) - เอื้อวงศ์กูล นันทวัน; รัตนมาลี ชนาพร; ดาดวง ศักดา (Progress in Applied Science and Technology, 2017)
The study of utilization of Tricholoma crassum to enhance growth and productivity of Ananas comosus cv. Pattawia was done. The experiment was divided into 7 groups as group 1 soil without sorghum and T.crassum, group 2, 3 and 4 soil with sorghum 100, 200 and 300 g/bag, respectively, group 5, 6 and 7 soil with T.crassum in sorghum 100, 200 and 300 g/bag, respectively. The study was done for 10 months and number of leaves, width of leaves, length of leaves, height, canopy diameter and survival rate wars determined every month. Finally, pineapple fruit was harvested. Length of fruit, diameter of fruit and weight of fruit was measured. The results revealed that group 6 soil with T.crassum in sorghum 200 g/bag had the highest number of leaves, length of leaves, height, length of fruit, diameter of fruit and weight of fruit as 51.1±6.5 leaves (p>0.05), 63.3±5.8 cm, 75.4±5.7 cm, 15.6±1.1 cm, 12.7±0.5 cm and 1,089.15±228.25 g, respectively (p<0.05). Group 5 soil with T.crassum in sorghum 100 g/bag had the highest width of leaves as 4.5±0.5 cm (p<0.05). Group 7 soil with T.crassum in sorghum 300 g/bag had the highest canopy diameter as 111.6±12.8cm (p>0.05). All groups had 100% survival rate and 100% rate of fruit set. Thus, using of T.crassum could be enhancing growth and productivity of Ananas comosus cv. Pattawia. Soil with T.crassum in sorghum 200 g/bag showed the highest potency to enhance growth and productivity of Ananas comosus cv. Pattawia.